2020
DOI: 10.3390/su12208536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sustainability Reporting and Inadequate Management of ESG Factors on Corporate Performance and Sustainable Growth

Abstract: The purpose of this research study is to examine and explain whether there is a positive or negative linear relationship between sustainability reporting, inadequate management of economic, social, and governance (ESG) factors, and corporate performance and sustainable growth. The financial and market performances of companies are both analyzed in this study. Sustainable growth at the company level is introduced as a dimension that depends on sustainability reporting and the management of ESG factors. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 111 publications
0
31
2
3
Order By: Relevance
“…Exploring the sustainability performances of companies using environmental, social, and governance scores was done by several researchers [2,3,9,10,41,64,65]. Used in addition to the financial score, the use of these scores increases accuracy in assessing performance and risk [64].…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
“…Exploring the sustainability performances of companies using environmental, social, and governance scores was done by several researchers [2,3,9,10,41,64,65]. Used in addition to the financial score, the use of these scores increases accuracy in assessing performance and risk [64].…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
“…The linkage between ESG scores and firm financial performance has been theoretically and empirically explored with inconclusive or contradictory results. Two conflicting theories seek to explain the effect of sustainability on firms' financial performance: value development (e.g., stakeholder theory, agency theory) and value destruction (trade-off theory) [21][22][23]. The approach to value-creation theory suggests that costs are minimized, competitive advantage is reinforced, reputation and legitimacy is developed, performance is maximized, and corporate risk is minimized with ESG disclosure [21,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Two conflicting theories seek to explain the effect of sustainability on firms' financial performance: value development (e.g., stakeholder theory, agency theory) and value destruction (trade-off theory) [21][22][23]. The approach to value-creation theory suggests that costs are minimized, competitive advantage is reinforced, reputation and legitimacy is developed, performance is maximized, and corporate risk is minimized with ESG disclosure [21,22,24]. On the other side, the value destruction hypothesis implies that ESG disclosure activity is costly and detrimental for shareholders [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking back on past research, Oprean-Stan, Oncioiu, Iuga and Stan [58] showed that the publication of nonfinancial metrics has a positive impact on traditional performance indicators such as return on assets. In fact, investments in renewables have fared better in the current crisis than investments in nonrenewables [4].…”
Section: Knowledge Contributionmentioning
confidence: 99%